The effect of different post-exercise beverages with food on ad libitum fluid recovery, nutrient provision, and subsequent athletic performance - McCartney, D.; Irwin, C.; Cox, G. R.; Desbrow, B. (Physiology & Behavior, 2019)
• Water and sports drink facilitate fluid recovery when consumed voluntarily with food between exercise bouts. • Consuming sports drink post-exercise increases total CHO and energy intake (from food and fluid). • However, the additional nutrition did not translate to improvements in subsequent cycling performance. • Recovery beverage recommendations should consider the post-exercise environment and athlete's nutritional needs.